2020
DOI: 10.18823/asiatefl.2020.17.3.14.966
|View full text |Cite
|
Sign up to set email alerts
|

Using Socrative for Vocabulary Tests : Thai EFL Learner Acceptance and Perceived Risk of Cheating

Abstract: Despite the growing interest in using online quizzes with Student Response System (SRS) for assessment, knowledge and empirical evidence about learner acceptance and risk of cheating are still limited in the literature. Hence, to address such gaps, this study explored Thai EFL learner acceptance and perceived risk of cheating of using Socrative for vocabulary tests. The participants (N = 461, 77.4% female, 22.6% male) attended a General English (GE) course that required them to learn fifty English words every … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…The second finding of this study indicates the possibility of cheating during online tests on Google Forms, where the participants confirmed the ease and existence of cheating when completing online tests. This finding aligns with those of the existing literature (King et al, 2009;Rowe, 2004;Özden, 2005;Rofiah & Waluyo, 2020). Despite cheating being a common phenomenon in any environment, it occurs to a more considerable extent in online assessment according to King et al (2009).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The second finding of this study indicates the possibility of cheating during online tests on Google Forms, where the participants confirmed the ease and existence of cheating when completing online tests. This finding aligns with those of the existing literature (King et al, 2009;Rowe, 2004;Özden, 2005;Rofiah & Waluyo, 2020). Despite cheating being a common phenomenon in any environment, it occurs to a more considerable extent in online assessment according to King et al (2009).…”
Section: Discussionsupporting
confidence: 91%
“…Many students felt more comfortable in online assessments and tended to cheat since what they did during the exam could not be seen (Rowe, 2004). Rofiah and Waluyo (2020) found that EFL students preferred using online quiz tools such as Socrative for vocabulary testing because it was easier to cheat; however, there was a lower probability of cheating among more proficient students. Therefore, although cheating is a common phenomenon in education that cannot be removed from online or traditional assessments, it does exist to a more considerable extent in online environments (King, et al, 2009).…”
Section: Perceived Risk Of Cheatingmentioning
confidence: 99%
See 3 more Smart Citations